Mary Lou Retton : power gymnast - Washington, Rosemary G. (Minneapolis : Lerner Publications, 1985)
Follows the training and career of Mary Lou Retton, the first American woman gymnast to win a gold medal in the Olympics.
8 11 13 18 31 38
Keywords: Retton, Mary Lou, -- 1968- -- Juvenile literature; Retton, Mary Lou, -- 1968-; Gymnasts -- United States -- Biography -- Juvenile literature; Gymnasts